2015
DOI: 10.1118/1.4903263
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐state dosimeters: A new approach for mammography measurements

Abstract: This study revealed that SStD measurements yielded good agreement with set kVp, poor agreement with standard HVL determinations, and AK measurements that were substantially different from IC measurements. Discrepancies are partly related to the scattered radiation measured by ICs in determining AK. As a result, IC measurements required for AGD, using currently accepted methodology, typically result in higher AGDs than SStDs, because current methodologies do not account for differing instrument responses to sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The selection of the tested dosimeters was made based on the limited information from the calibration laboratories in order to cover some of the most common models. This selection is comparable with the study of Brateman and Heintz and includes dosimeters that have been marketed for a long time as well as more recent models.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The selection of the tested dosimeters was made based on the limited information from the calibration laboratories in order to cover some of the most common models. This selection is comparable with the study of Brateman and Heintz and includes dosimeters that have been marketed for a long time as well as more recent models.…”
Section: Discussionmentioning
confidence: 70%
“…With increased dose rate, X2 measured the tube voltage for Mo‐Rh 30 and 35, but still failed for Mo‐Rh 28. The performance of tube voltage measurement of semiconductor dosimeters on clinical mammography units was investigated by Brateman and Heintz . There, Xi also failed to derive tube voltage from measurements for W‐Ag on the clinical mammography units.…”
Section: Discussionmentioning
confidence: 99%
“…This detector is generally designed for diagnostic radiography (13) . The source‐to‐detector distance (SDD) was 226.4 cm, and the detector‐to‐imager distance (DID) was 236.8 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, a variety of semiconductor dosimeters are commercially available. In the literature, the results for the ionisation chamber and semiconductor dosimeter show differences ranging from 4.3% to 13.4%, depending on the type of semiconductor detector used for the MGD [19]. Therefore, an HD-M can provide accurate measurements similar to commercial products that are in the range of the measuring tube voltage (24 kV to 32 kV) with Mo-Mo target filter.…”
Section: Energy Characteristicsmentioning
confidence: 99%
“…In recent years, there have been many reports that semiconductor dosimeters are useful in daily QC during general imaging [11,[15][16][17][18]. However, in the case of semiconductor dosimeters, the response varies depending on the energy of the x-rays [19]. For mammography, there are many reports that have indicated that the response changes significantly owing to differences in x-ray energy, and that the target-filter combination is limited [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%